2014
DOI: 10.1111/1759-7714.12085
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Icotinib treatment in patients with stage IIIb/IV non‐small cell lung cancer

Abstract: Background: To evaluate the efficacy and safety of Icotinib -an orally administered, highly potent selective inhibitor of epidermal growth factor receptor (EGFR) and its active mutations, in the treatment of patients with advanced non-small cell lung cancer (NSCLC). Methods: A total of 101 patients with stage IIIb/IV NSCLC were treated with 125 mg Icotinib three times a day until disease progression or intolerable toxicity. Response rate was evaluated using response evaluation criteria in solid tumors and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Seven studies [1418, 20, 22, 24] concerning the relationship between the PFS and prior chemotherapy showed that the PFS of first line group (10.1 months) and the second line (7.1 months) did not have a statistical difference when they received icotinib ( t = 1.59, df = 12, p = 0.13) (Figure 3D). …”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [1418, 20, 22, 24] concerning the relationship between the PFS and prior chemotherapy showed that the PFS of first line group (10.1 months) and the second line (7.1 months) did not have a statistical difference when they received icotinib ( t = 1.59, df = 12, p = 0.13) (Figure 3D). …”
Section: Resultsmentioning
confidence: 99%
“…Several phase I and II studies of icotinib in treatment of BM have been published recently. Zhou et al reported that icotinib could be well tolerated at dose of 375mg tid/day concurrent with WBRT in a phase I study, and found that the mean icotinib cerebrospinal fluid (CSF) penetration rate was 4.04% (range: 1.23%–9.71%) [ 22 ]. A phase II study of icotinib combined with WBRT treatment found that the CSF concentration and penetration rate were 11.6 ± 9.1 ng/mL and 1.4 ± 1.1% respectively at a dose of icotinib 125mg tid.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of chemotherapy and the radiotherapy for non-small cell lung carcinoma tends to be low, and surgical resection of cancer is mainly applied for patients in early stage non-small cell lung carcinoma (1-3). Combination chemotherapy is carried out in addition to the surgical resection of cancer for an advanced non-small cell lung carcinoma (1,(3)(4). The main anti-cancer drug in chemotherapy for non-small cell lung carcinoma is cisplatin (1,3).…”
Section: That Trehalose Liposomes (Dmtrec14) Composed Of L-α-dimyristmentioning
confidence: 99%
“…Combination chemotherapy is carried out in addition to the surgical resection of cancer for an advanced non-small cell lung carcinoma (1,(3)(4). The main anti-cancer drug in chemotherapy for non-small cell lung carcinoma is cisplatin (1,3). Cisplatin-combination chemotherapy use irinotecan, paclitaxel, gemcitabine and vinorelbine (1,3).…”
Section: That Trehalose Liposomes (Dmtrec14) Composed Of L-α-dimyristmentioning
confidence: 99%
See 1 more Smart Citation